Thermal performance analysis of a mixed-flow indirect evaporative cooler. (25th November 2022) - Deepak, C.; Naik, Rudra; Godi, Sangamesh C.; Mangrulkar, Chidanand K.; H.K., Prashanth
Abstract: This study experimentally investigates the performance of an indirect evaporative cooler based on the Maisotsenko cycle. It consists of a heat and mass exchanger (HMX) with a novel mixed-flow configuration. The de-sized cellulose rich cotton fabric is used as water-absorbing material, and aluminum sheets are used to fabricate the heat mass exchanger unit. The cooling performance indices of the system, namely dew point effectiveness (DPE), wet bulb effectiveness (WBE), and the coefficient of performance (COP), are evaluated at different inlet air temperatures (24 to 35 °C), volumetric flow rates (600 to 1050 m 3 /h), relative humidity (35 to 65%) and the extraction ratio (0.1 to 0.6). The results of the experimental study show that at a relative humidity of 35%, and inlet air temperature of 35 °C, the magnitude of the wet bulb and dew point effectiveness are highest and higher dew point and wet bulb effectiveness are observed at lower mass flow rates. The best cooling capacity and COP were obtained at an extraction ratio of 0.3 and are found to be highest at DBT of 35 °C. The maximum magnitude of CC was 2 kW with a COP of 16. Additionally, the convective heat transfer coefficient is calculated theoretically and compared with the experimental value. Further, a comparison of the obtained results for the mixed flow configuration considered in this study with those for other configurations reported in the literature reveals that the indirect evaporative cooler with mixed-flow configuration yields comparably good effectiveness. Highlights: Performance of indirect mixed flow evaporative cooler evaluated experimentally. Effect of temperature, flow rate, relative humidity and extraction ratio are studied. The optimum extraction ratio is observed to be 0.30. Better performance is at higher inlet air temperature with lower humidity. The maximum COP of 16 was observed at 35 °C with 35% relative humidity.